The influence of alcohol on basic motor and attention-perceptual abilities - Ivanec, Dragutin (Array, 2008)
The aim of the study was to investigate effects of different levels of the blood alcohol concentration on the performance in the three basic motor and attention perceptual tasks. Participants (N=24, repeated measurement design) were tested at the four levels of the blood alcohol concentration: placebo ; 0.3 ; 0.5 and 0.8 g/kg. In every single measurement, participants were performing three different tasks: go-no-go reaction time task, the test of perceptual speed and the classical Stroop task. Those three tasks were chosen due to the different levels of perceptual, motor and cognitive-attention abilities they are proven to include. Results showed that different effects of the blood alcohol concentration have statistically significant and linear effect on the performance in go-no-go reaction time task and the test of perceptual speed. As alcohol concentration increased, reaction time decreased and perceptual speed was more impaired. For the classical Stroop task, effect of alcohol consumption was also significant but obtained function was quadratic, not linear. Amount of interference was the same for the non-alcohol (placebo) and highest alcohol (0.8 g/kg) blood concentration level and interference in those two situations was smaller then those obtained at mid (0.3 and 0.5 g/kg) alcohol concentration levels. According to these results, Stroop performance is more impaired at moderate then at higher level of alcohol consumption. At higher level, results are similar to those obtained for non-alcoholic consumption. The influence of different alcohol levels was statistically significant for all three tasks. Size effects were also high, but in terms of differences on absolute measurement unit, effects were small.